EVALUATION OF LOW ATTENDANCE OF MEMBERS DURING WEEKLY GROUP MEETINGS AT PERMODALAN NASIONAL MADANI (PNM) MEKAAR SOLO - Seno, Ananto (UTSAHA: Journal of Entrepreneurship, 2023)
This research evaluated the low attendance of members during weekly group meetings at Permodalan Nasional Madani (PNM) Mekaar in Solo. This research aims to determine the factors that inhibit group members from attending weekly group meetings and identify policies taken by PNM Mekaar to ensure weekly group meetings stay active. Purposive sampling was used to select the research subjects, who must have joined PNM Mekaar at least since 2020, be registered as customers at PNM Mekaar, be registered as employees at PNM Mekaar for at least six months, and have agreed to participate in the research. Based on the findings, internal and external factors contributed to the problem of group members who had to attend weekly group meetings. These internal factors included less friendly account officers, no ceremonial weekly group meetings, weekly group meetings starting to focus solely on instalments, overworked account officers, new account officers still in training, high member turnover within three months, senior account officers and account officers not outlining key points of the cooperation agreement, and PT PNM Mekaar delegating the responsibility of customer education to the group leader. Meanwhile, other external factors, which include customers’ busy schedules and the laziness of some customers after years of paying instalments, prevent group members from attending weekly group meetings. PNM Mekaar's policy of delegating customer evaluation to its officers allows the weekly group meetings to operate as usual.